2015
DOI: 10.1177/1475725714564925
|View full text |Cite
|
Sign up to set email alerts
|

Helping preservice teachers with inaccurate and fragmentary prior knowledge to acquire conceptual understanding of psychological principles

Abstract: Psychological research on learning has brought forth many insights that are relevant for teachers (for example, knowledge about learning strategies). However, teachers sometimes have intuitive fragmentary knowledge that is partly incorrect. Such knowledge hinders the acquisition of psychological knowledge. Tried-and-tested interventions dealing with fragmentary knowledge remain scarce and thus a generalized categorical framework was developed to support preservice teachers to (re)organize their fragmentary pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 64 publications
0
7
0
2
Order By: Relevance
“…& Reflection phases were coded as included if learners were encouraged to think about the goals of the procedure, analyze their own performances, and plan further steps, or "not included." Bahreini et al, 2013Besser et al, 2015Chamberland et al, 2011Chamberland et al, 2015aChamberland et al, 2015bEva et al, 2007I Eva et al, 2007II Gold et al, 2013Gutierrez-Maldonado et al, 2014Heitzmann et al, 2013Heitzmann et al, 2015Heitzmann et al, 2018aHellermann et al, 2015Ibiapina et al, 2014I Ibiapina et al, 2014II Jarodzka et al, 2012Klug et al, 2016Krammer et al, 2016Liaw et al, 2010Mamede et al, 2012Neistadt & Smith, 1997Ohst et al, 2015I Ohst et al, 2015II Papa et al, 2007Peixoto et al, 2017Raupach et al, 2010I Raupach et al, 2010II Raupach et al, 2013I Raupach et al, 2013II Round, 1999Stark et al, 2011I Stark et al, 2011II Sunder et al, 2016 29 studies (reporting 35 independent experiments) included in the analysis Fig. 1 Flow chart of the study selection process Diagnostic situation included the (a) information base, which was coded as "interactionbased" if information to diagnose was gathered through real or simulated interactions; as "document-based" if information was gathered from a document or a video with diagnostic information without a possibility to interact; and (b) processing mode, which was coded as "collaboration" if collaboration during the diagnostic process was necessary, or as "individual" if diagnosis/decision was achieved by a...…”
Section: Coding For the Moderatorsmentioning
confidence: 99%
“…& Reflection phases were coded as included if learners were encouraged to think about the goals of the procedure, analyze their own performances, and plan further steps, or "not included." Bahreini et al, 2013Besser et al, 2015Chamberland et al, 2011Chamberland et al, 2015aChamberland et al, 2015bEva et al, 2007I Eva et al, 2007II Gold et al, 2013Gutierrez-Maldonado et al, 2014Heitzmann et al, 2013Heitzmann et al, 2015Heitzmann et al, 2018aHellermann et al, 2015Ibiapina et al, 2014I Ibiapina et al, 2014II Jarodzka et al, 2012Klug et al, 2016Krammer et al, 2016Liaw et al, 2010Mamede et al, 2012Neistadt & Smith, 1997Ohst et al, 2015I Ohst et al, 2015II Papa et al, 2007Peixoto et al, 2017Raupach et al, 2010I Raupach et al, 2010II Raupach et al, 2013I Raupach et al, 2013II Round, 1999Stark et al, 2011I Stark et al, 2011II Sunder et al, 2016 29 studies (reporting 35 independent experiments) included in the analysis Fig. 1 Flow chart of the study selection process Diagnostic situation included the (a) information base, which was coded as "interactionbased" if information to diagnose was gathered through real or simulated interactions; as "document-based" if information was gathered from a document or a video with diagnostic information without a possibility to interact; and (b) processing mode, which was coded as "collaboration" if collaboration during the diagnostic process was necessary, or as "individual" if diagnosis/decision was achieved by a...…”
Section: Coding For the Moderatorsmentioning
confidence: 99%
“…Applied to teacher's knowledge as self-regulated learners it can be stated, that teachers' metacognitive knowledge as well as their awareness about strategies and metacognition itself are crucial. This knowledge and awareness build a basis for the development of metacognitive skills and relates to the promotion and support of metacognition and SRL (Paris and Winograd, 2003;Moos and Ringdal, 2012;Ohst et al, 2015). Wilson and Bai (2010) asserted that teachers must possess a deep understanding of metacognition in order to provide opportunities for metacognitive development in classroom.…”
Section: Teachers' Knowledge As Self-regulated Learnersmentioning
confidence: 99%
“…Regrading CK-SRL, studies with pre-service teachers and in-service teachers from different educational levels reported that teachers lack knowledge about the concept of SRL (Waeytens et al, 2002;Askell-Williams et al, 2012;Spruce and Bol, 2015). This lack of knowledge ranges from holding misconceptions or possessing only fragmented knowledge about strategies and metacognition (Zohar, 1999;Ohst et al, 2015;Glogger-Frey et al, 2018). Dignath and Büttner (2018) revealed that primary and secondary school teachers found it difficult to define different strategies and hold more knowledge about cognitive than metacognitive strategies.…”
Section: Teachers Knowledge As Agents Of Srlmentioning
confidence: 99%
“…Yet, as noted earlier, concerns about the effectiveness of this instruction for impacting on teacher knowledge and teaching practice have emerged in studies involving both pre‐service and practising teachers. Both Ohst, Glogger, Nuckles, and Renkl (2015) and Glogger‐Frey, Ampatziadis, Ohst, and Renkl (2018) found that their pre‐service teachers had poor‐quality knowledge of learning strategies. Studies that have involved observation of practising teachers in different countries have shown infrequent or negligible teaching about SRL and use of SRL principles in teaching (e.g., Cleary & Kitsantas, 2017; Dignath & Büttner, 2018; Moely et al , 1992; Spruce & Bol, 2015).…”
Section: Conclusion Limitations and Future Directionsmentioning
confidence: 99%